Evaluasi Beban Kerja Manual (Studi Kasus UD Sumber Makmur Medan) - Kimberly Febrina Kodrat (Jurnal Teknik Industri, 2013)
UD Sumber Makmur is one of the home industries producing snacks especially cassava chips with various kinds of flavor. Packaging process is still performed manually through utilizing the physical power of workers. This research aims to evaluate manual workload in the particular tasks. The research object includes two groups of task which are group A (associated with production tasks) and group B (associated with packaging tasks). According to the result, it shows that average physical workload in both groups is constants and it is included in light-medium work category. The break time required by workers in group A and B respectively is 31 minutes and 45 minutes.